Analysis Of Village Fund Management In Realizing Good Governace (Study In Pelauw Village In Pulau Haruku District) - Rasyid Latuconsina; Paul Usmany; Salomi Jacomina Hehanussa (LP2M IAIN Palopo, 2026)
This study aims to analyze the management of Village Funds in realizing good governance in Pelauw Village, Pulau Haruku District. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation, with key informants including the Village Head, Village Secretary, Village Treasurer, Village Consultative Body (BPD), and community leaders. Data analysis was conducted using interactive analysis techniques by Miles, Huberman, and Saldana, which include data reduction, data presentation, and conclusion drawing. The results show that the management of Village Funds in Pelauw Village does not fully reflect the principles of good governance. Transparency of financial information is still limited, accountability for budget realization reports is not consistent with regulations, and community participation in village deliberations is often merely a formality. The main obstacles faced include limited capacity of village officials, lack of utilization of information technology such as the SISKEUDES application, and weak community oversight mechanisms. This study concludes that to realize transparent, accountable, and participatory management of Village Funds, it is necessary to strengthen the human resource capacity of village officials, provide supporting information technology facilities, and increase public awareness of their important role in planning and monitoring village development